2019
DOI: 10.7717/peerj.7719
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for patients with acute respiratory distress syndrome: use of a genetic algorithm to develop a neural network model

Abstract: Background Acute respiratory distress syndrome (ARDS) is associated with significantly increased risk of death, and early risk stratification may help to choose the appropriate treatment. The study aimed to develop a neural network model by using a genetic algorithm (GA) for the prediction of mortality in patients with ARDS. Methods This was a secondary analysis of two multicenter randomized controlled trials conducted in forty-four hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…These two studies on ARDS indicated that ML was superior to the traditional APACHE score; however, the robustness requires further validation owing to the relatively small sample size or lack of multi-source validation. Similarly, our results demonstrated the ability of ML to predict the mortality of patients with ARDS, achieving comparable or even better performance than Ding et al (13) and Zhang (14) in a larger and multisource dataset. Compared with existing scoring systems, the RF-based algorithm has the following advantages.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These two studies on ARDS indicated that ML was superior to the traditional APACHE score; however, the robustness requires further validation owing to the relatively small sample size or lack of multi-source validation. Similarly, our results demonstrated the ability of ML to predict the mortality of patients with ARDS, achieving comparable or even better performance than Ding et al (13) and Zhang (14) in a larger and multisource dataset. Compared with existing scoring systems, the RF-based algorithm has the following advantages.…”
Section: Discussionsupporting
confidence: 74%
“…Ding et al (13) built an RF model to predict ARDS events in a small sample of 296 patients, and achieved an AUROC of 0.82. Zhang (14) developed a neural network model with a genetic algorithm to predict 90-day mortality in a database of 745 patients, and in the testing cohort of 272 patients achieved an AUROC of 0.821. These two studies on ARDS indicated that ML was superior to the traditional APACHE score; however, the robustness requires further validation owing to the relatively small sample size or lack of multi-source validation.…”
Section: Discussionmentioning
confidence: 99%
“…The top 5 features in the model were minimum tidal volume, Glasgow coma score, respiratory rate, P aO 2 , and age. 31 In a secondary analysis of 2 multi-center RCTs from 44 hospitals, Zhang 32 conducted a study in the same area. However, rather than predict development of ARDS, the author sought to predict mortality following diagnosis of ARDS and to provide risk stratification in an effort to help clinicians choose appropriate treatment.…”
Section: Ardsmentioning
confidence: 99%
“…Algorithms used for the prediction of ARDS include mostly supervised ML algorithms including regression [ 15 ], classification [ 17 ], decision trees [ 17 , 19 ], or neural network [ 20 ]. There have also been attempts to identify ARDS with the help of unstructured data such as text from radiology reports using natural language processing and ML [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, it is claimed to be relatively easy to use and does not require mathematical operations. Another approach using a genetic algorithm was developed by Zhan, who identified seven important variables (age, AIDS, leukemia, metastatic tumor, hepatic failure, lowest albumin, and FiO 2 ) for the prediction of mortality in ARDS patients [ 20 ]. These approaches achieved comparable performance to widely used APACHE III scoring in predicting mortality of patients in hospitals admitted with ARDS.…”
Section: Reviewmentioning
confidence: 99%